Does Environmental Kuznets Curve Hypothesis Hold for ASEAN-5? - Tan, Hui Meia (2009)
This study examines the impact of various factors such as income and foreign direct investment on environment quality in the ASEAN-5 Countries. GDP per capita will be used as proxy for income while sulfur dioxide and carbon dioxide emission will be used as proxy for pollution. The extended environmental Kuznets curve (EKC) was employed, utilizing the available time series data from 1970 to 2000 for Indonesia, Malaysia, Philippines, Thailand and Singapore. The results indicate EKC is not generally fit for all ASEAN-5 countries and instability of the EKC shape is observed when different range of data, different pollutant and different econometrical strategy are used.